Arterial segments as microvascular interposition grafts in venous anastomosis in digital replantations - Shiv Shankar Saha; Anurag Pandey; Chirayu Parwal (Indian Journal of Plastic Surgery)
Introduction: Microvascular anastomosis is a crucial procedure in replantation surgeries. Venous insufficiency is one of the most consistent cause of failure or re-exploration in these surgeries necessitating the use of venous grafts. Materials and Methods: We discuss our study of 9 such replantation surgeries executed in calendar year 2013-2014, including a double finger replantation done in the same patient having total amputation of 4 fingers of the same (right) hand, in which an arterial segment was used as a microvascular interposition graft for venous anastomosis. Out of these 9 surgeries, 3 were re-exploration procedures for venous compromise and 6 were successful primary replantations. Results: In all, 8 replants were successful and one failed due to arterial compromise. Discussion: In our experience and extensive review of the previously available literature, we would like to portray the advantages of arterial segments as microvascular grafts in replant surgeries. Specifically, in a crush amputation injury for which the use of a vascular interposition graft is being contemplated. If any other digit is also amputated and is unsuitable for replantation, it can act as a potential donor site to harvest the arterial segment. However, when dealing with single finger amputation, the surgeon must be confident about the single digital arterial anastomosis, before harvesting the second digital artery as a microvascular graft. Conclusion: In our study, we found the use of arterial grafts in microvascular anastomosis of veins advantageous, as arterial segments have better ability to resist spasm due to environmental changes, better pressure tolerance as compared to venous segments, and provide an appropriate calibre match and ease of harvest in the same operative field.